The network analysis of organizations in watershed management toward sustainability in Northern Iran - Rezaei-Moghaddam, Kurosh; Fatemi, Mahsa (Frontiers in Environmental Science, 2023)
The integrated water resource management is considered for development planning and water and soil resources management with an emphasis on the socio-economic features of the region for sustainability. The main purpose of study was to identify the organizations involved in the watershed management of Chehelchay of Golestan province in Iran, as well as analyzing the types of communications and interactions between organizations in terms of intensity and type. Three networks of information exchange, coordination and participation were studied due to network analysis. Thus, the related organizations involved in participatory and comprehensive management of Chehelchay watershed (30 organizations) were introduced during the trips of the research team to the site and using special questionnaire. Then, the other specialized questionnaires were collected from the informed panels of each organization to provide the required data in the network analysis. A total of 84 specialists were interviewed. About half of the respondents (42 individuals) had graduate education and their average work experience was about 15 years. One third of the respondents (28 individuals) were women. The data analysis process was performed with UCINET6.631 and NetDraw. The results indicated that the density index in information exchange (31.5%), coordination (27.3%) and participation (10%) networks were less than average. In the participation network, the values of the density index are very low and coherence is the same among the networks (information exchange, coordination, and participation). The results of reciprocity index among the organizational actors in the networks of information exchange (31.10%), coordination (33.52%) and participation (10.13%) were also less than average. Therefore, identifying the key actors with high social power in the network of local natural resources is a requirement of watershed participatory management plan. The runtime and cost of implementing natural resource projects can be significantly decreased by understanding and deploying these organizations and individuals. Social power and comprehensive participatory management is generally the key tools for building trust between local natural resource users. A systematic shift is also required from governmental management toward governance in order to achieve sustainable natural resource and watershed management